Evaluation of salt (NaCl) concentrations in irrigation water on lettuce (Lactuca sativa L.) ‘Batavia’ growth - Lesmes, Ricardo; Molano, Ángela; Miranda, Diego; Chaves, Bernardo (Sociedad Colombiana de Ciencias Hortícolas-SCCH and Universidad Pedagógica y Tecnológica de Colombia-UPTC, 2011)
Growth of lettuce ‘Batavia’ was evaluated at different salt concentrations in water irrigation under hydroponic conditions in the Bogotá plateau comparing the use of two substrates: blonde peat and a mixture between rice husk and blonde peat in 1:1 ratio. The evaluated variables: plant height, plant leaves number, dry weight, fresh weight and leaf area. These variables ere used to state the growth parameters: Leaf area index (LAI), specific leaf area (SLA), net assimilation rate (NAR), growth absolute rate (GAR), growth relative rate (RGR) and crop growth rate (CGR). Difference was observed pronounced in the height of the plant between treatments, being higher the height of plants sowed in peat. The biggest leaf number appeared in the plants established in peat without addition of NaCl, with 35 leaves in average. There was a reduction in foliar area as salt concentrations were increased. It was observed that the reduction of the leaves dry weight of plants established in mixed substrates was 38%, with regard to the treatments established in peat. The salinity affects vegetative and reproductive stages of development and also causes reductions both in the biomass and in the yield of the culture. The best responses for all salt concentrations in the growth parameters, dry weight, and biomass accumulation were reported for plants sowed in blonde peat, due to a more controllable salinity in this substrate.